2019
DOI: 10.1177/2057158519877794
|View full text |Cite
|
Sign up to set email alerts
|

The significance of communication and care in one’s mother tongue: Patients’ views

Abstract: Language barriers in the healthcare sector, for example as a result of failure to use a patient’s mother tongue, can lead to misunderstandings and/or care errors, especially when circumstances require that nursing staff or patients speak a language other than their own mother tongue. The aim of this study was to explore the importance of patients receiving care in their mother tongue. A hermeneutic approach was used and the method was inspired by content analysis. The data material was collected through semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This was consistent with a study that showed providing care in a patient’s primary language improved communication, built trust and enhanced the quality of care. 32 Therefore, learning basic medical terms in patients’ native language offers an innovative and effective solution to address the language barrier issue and improve healthcare services for Arab patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with a study that showed providing care in a patient’s primary language improved communication, built trust and enhanced the quality of care. 32 Therefore, learning basic medical terms in patients’ native language offers an innovative and effective solution to address the language barrier issue and improve healthcare services for Arab patients.…”
Section: Discussionmentioning
confidence: 99%
“…The participants generally had no problems with health terminology, which was also expected, considering them being pharmacists and pharmacy students, but they mentioned that they have encountered some content-level challenges (complex/foreign language and tools) which they recognized as room for app optimization. Apps being recognized as complicated and unavailable in the local language can be a challenge, especially if these apps were to be recommended to the general population because patients appreciate communication and care in their mother tongue (Hemberg & Sved, 2021 ) and most users of pharmaceutical services are not digitally literate (International Pharmaceutical Federation [homepage on the Internet], 2022 ). This is especially important for the Republic of Serbia, considering that in the report from 2019, it was stated that almost one quarter of respondents never used the internet (Team for social inclusion and poverty reduction of the Government of the Republic of Serbia [homepage on the Internet], 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It will encourage them to recount their experiences (cerita), explore their emotions (emosi), critically evaluate their actions (rasional), draw meaningful lessons and take initiative (mengambil iktibar/inisiatif), and prioritise their initiatives (nomborkan inisiatif mengikut prioriti). By offering a framework that resonates with their cultural and linguistic background, students will be more likely to internalise and apply the stages in their professional development (Hemberg & Sved, 2019).…”
Section: Discussionmentioning
confidence: 99%